The Effect of Providing Information About Ca Cerviks via Whatsapp Autoreply on the Interest of Women of Childbearing Age to Conduct IVA Screening at the Bandar Health Center in 2024 - Seprianti, Monica Eprita; Fitriani, Arifah Devi; Asriwati, Asriwati (PROMOTOR, 2025)
The high prevalence of cancer in Indonesia needs to be observed with preventive measures and early detection through Visual Examination of Acetic Acid/IVA test. The low interest of women of childbearing age to do IVA Screening is one of the health problems. Many media have been used by the government and researchers before to socialize cervical cancer prevention to the public. In the digital era, the internet is one of the dominant information media, the most accessed is WhatsApp (95.9%). Researchers use the Whatsapp autoreply feature to provide information about Ca Cervix which can be accessed 24/7. The use of this technology is expected to be useful so that users are motivated to conduct IVA screening. The study used a quasi experiment with a pretest-posttest control group design model. The data were analyzed using the non-parametric statistical test Wilcoxon Signed Rank Test to compare the differences between the pre-test and the post-test and the Mann Whitney U Test to compare the differences between the control group and the experimental group. In the control group, the results of the wilcoxon test pre-test post-test knowledge context showed a-Symp 0.227, at the input information a-Symp 0.916, in the process of providing information a-Symp 0.083 and at Interest a-Symp 0.317, the value was >0.05 Ho was rejected, there was no difference in the pre-test post-test of the control group. In the experimental group, the results of the wilcoxon test pre-test post-test in the context of knowledge, showed a-Symp 0.000, at the input of a-Symp information 0.000, in the process of providing information a-Symp 0.000 and in the interest of a-Symp 0.000, the value <0.05 Ho was accepted, there was a difference in the pre-test post-test of the experimental group. The results of the Mann Whitney U Test showed that A-Symp was 0.000< 0.05 There was a difference in the control group and there was an increase in the experimental group that was given the treatment. The interest of women of childbearing age to do IVA screening can increase after being given information about Ca Cerviks and IVA Test through whatsapp autoreply.